Teachers’ Perceptions Towards Assessing Learners’ Intercultural Communicative Competence in the EFL Classroom in Algeria - Hamadouch, Abed; Aoumeur, Hayat (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
This research seeks to highlight the perceptions of English as a Foreign Language (EFL) teachers in Algeria regarding the assessment of learners’ ICC. In the classroom. Additionally, this research proposes some suggestions on how to teach and assess middle school learners to be interculturally competent. To achieve this objective, a qualitative research design is employed to gain data. The data source of this study was eleven English middle school teachers from different middle schools in Algeria. The study applied an interview utilizing open-ended questions to see their responses about their perceptions and attitudes toward the assessment of their learners. The data collected was thematically analyzed to identify recurring patterns, challenges, and emerging themes related to the assessment of ICC in the EFL classroom. The results show teachers need training on developing communicative tasks for teaching culture that can help them assess their students’ intercultural communicative competence. So, the lack of continuing professional development in pre-service and in-service makes them wander when teaching their learners about the target language and its culture. In addition to this, data show that teachers assess their learners in terms of grammar, pronunciation, general knowledge about the target culture, and vocabulary, but they do not assess their ICC. The implications of this study extended to both pedagogical practices and educational policy in Algeria. By understanding teachers’ perceptions, this research contributes valuable information to the ongoing discourse on fostering intercultural competence in language education. The findings may guide curriculum development, teacher training programs, and assessment practices, ultimately enhancing the effectiveness of EFL instruction in Algeria.